Dietary sodium intake and sweat sodium losses in endurance athletes - Gotthold, C. (West Chester University, 2020)
Context: Sweat rate and sodium concentration has been investigated previously for endurance athletes; however, dietary sodium intake has not been researched. Endurance athletes who have high sweat rates may need to supplement sodium in their diet in order to maintain fluid and sodium balance. Objective: To calculate daily sodium intake for cross country runners over three consecutive days of training and compare them to sweat sodium losses during the three training sessions. Design: Observational field study Participants: Ten athletes (age = 20.5 ± 1.51, height = 173.21 ± 12.66 cm, mass = 65.51 ± 10.60kg) participated. Interventions: Sweat rate was calculated by change in body weight adjusted for fluid consumed and length of training. Sterile sweat patches were used to collect sweat samples from the forearm and low back. The patches were removed post training session, placed in sterile tubes and centrifuged. Sweat was analyzed for sodium and chloride by ion-selective electrode. Diets were analyzed using a common nutrition analysis software, ESHA. Main Outcome Measurements: Sweat rate, sweat losses, sweat sodium and chloride concentrations, daily sodium and salt (NaCl) losses, daily dietary sodiumintake, calculated NaCl intake, and body mass. Results: On all experimental days, sodium intake exceeded sodiumloss. Calculated sweat rates displayed variability that ranged from 0.19 - 1.40 L/h. Mean sweat sodium concentration was 60.44 ± 27.76 mmol/L (3.71 ± 1.88 g) and ranged from 1.4-6.63 grams. Conclusion: Participant body weight remained consistent (day 1= 65.61 ± 10.48 kg, day 2= 65.51 ± 10.60 kg, day 3= 65.70 ± 10.48 kg). All runners` dietary sodium intake was greater than measured sweat sodium losses indicating that they maintained sodium and fluid balance during these three days without the need for electrolyte replacement.